Current approaches and tools for combating antibiotic resistance - Mmbando, Gideon Sadikiel; Ally, Ombeni; Misinzo, Gerald (Discover applied sciences, 2025)
Antimicrobial resistance (AMR) is a serious global health concern that requires a wide range of strategies and tools to combat resistant pathogens successfully. Yet, there is a gap in the knowledge regarding up-to-date approaches for combating AMR. This review highlights the most effective tools and strategies for combating AMR, including vaccination, bacteriophage (phage) therapy, antibiotic stewardship, antimicrobial peptides, and development of new antibiotics. This study found that programs for antibiotic stewardship are crucial for maximizing the use of antibiotics, minimizing their misuse, and halting the development of resistance. Vaccination is also essential in averting infections, lowering the demand for antibiotics and the risk of AMR. Moreover, phage therapy provides a focused method for eliminating resistant bacteria. Broad-spectrum antimicrobial peptides show promise because they are less susceptible to resistance mechanisms and activity by bacteria. Drug delivery to infection sites can be facilitated by nanoparticles' customizable qualities, which also improve efficacy and minimize side effects. This review emphasizes how crucial it is to consider a multiple, holistic approach to effectively combat the growing threat posed by AMR.